Analisis Faktor Fundamental Terhadap Praktik Internet Financial and Sustainability Reporting (IFSR) - Lisa Agustina Leonardi; Berkat Zeth Betaubun; Puspita Novi Tiyana; Dian Suryanti; Puput Indrayani; Theresia Purbandari (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2016)
Abstract:This study aimed to examine the effect of firm size, profitability, leverage, liquidity, and ownership outsiders to Interenet Financial and Sustainability Reporting (IFSR) . A sample of 125 companies were selected based on certain criteria that is listed on the Indonesia Stock Exchange that have a personal website as well as the financial statements are published on the Internet during 2010 to 2012. The hypothesis testing by using multiple linear regression analysis . Results of hypothesis testing is firm size significant positive effect on the application of IFSR practices, while variable profitability, leverage, liquidity, and ownership outsiders does not affect the application of IFSR practices.Abstrak: Penelitian ini bertujuan untuk menguji pengaruh ukuran perusahaan, profitabilitas, leverage, likuiditas, dan kepemilikan pihak luar terhadap Interenet Financial and Sustainability Reporting(IFSR). Sampel sebanyak 125 perusahaan yang dipilih berdasarkan kriteria tertentu yaitu terdaftar di Bursa Efek Indonesia yang memiliki websitepribadi serta laporan keuangan yang dipublikasikan di internet selama tahun 2010 sampai tahun 2012. Teknik pengujian hipotesis dengan menggunakan analisis regresi linier berganda. Hasil pengujian hipotesis adalah ukuran perusahaan berpengaruh positif signifikan terhadap penerapan praktik IFSR, sedangkan variable profitabilitas, leverage, likuiditas, dan kepemilikan pihak luar tidak berpengaruh terhadap penerapan praktik IFSR.Pengutipan: Leonardi, L. A., Betaubun, B. Z., Tiyana, P. N., Suryanti, D., Indrayani, P., Purbandari, T. (2016). Analisis Faktor Fundamental Terhadap PraktikInternet Financial and Sustainability Reporting (IFSR). SOSIO DIDAKTIKA: Social Science Education Journal, 3(1), 2016, 37-49. doi:10.15408/sd.v3i1.3796.Permalink/DOI: http://dx.doi.org/10.15408/sd.v3i1.3796